Ações regressivas acidentárias sob a perspectiva da previdênca social e da responsabilidade civil - Correia, Larissa Soldate [UNESP] (2015)
The protection of workers' health is the subject of several rules about security and protection related to the work environment. When disregarded by employers, may give rise to indemnifications in the civil sphere to the worker, imposition of fines by the Ministério do Trabalho e Emprego, filing of class actions initiated by the Ministério Público do Trabalho and regressive collection of the amounts spent by the Instituto Nacional do Seguro Social (INSS) with the benefits granted to the injured worker. This collection of Social Security autarchy's initiative, established under Article 120, from the Law No. 8.213/1991, is achieved through the filing of the accident actions to recover (ARAs) and constitutes the core object from this research. More specifically, this study aims to analyze the compatibility of the ARAs with the Brazilian social security model, characterized by division, solidarity as to the social risk and plurality of the funding sources. To achieve this purpose will be used as basis the principles and rules governing the Regime Geral da Previdência Social and the typical institutes of civil liability likely to be applied in the public area. Furthermore, it is intended to ascertain if ARAs are the most appropriate and effective legal instrument to achieve its purposes: the punitive- indemnifying and the preventive-pedagogical. As it is a controversial matter, other material and procedural aspects linked to the ARAs will also be covered in this research, such as: legal nature, jurisdiction, statute of limitation, evidential burden, capital formation, proposal of legal action against micro and small enterprises and in cases of strict liability of the employer, in addition to the passive legitimacy of these actions in cases of domestic violence, on conviction by Maria da Penha's Law, and automobile accidents